Dampak Pelaksanaan Kurikulum Merdeka Belajar Bagi Guru Di MTSN 2 Solok Selatan - Nur Putri Khalbi; Lutfi Alvina; Merika Setiawati; Luthfiani Luthfiani (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
The change from the K13 Curriculum to the Independent Learning Curriculum has had positive and negative impacts for MTSN 2 Solok Selatan teachers. The positive impacts include increasing teacher motivation and enthusiasm for teaching, giving teachers freedom and autonomy in designing learning, increasing teacher creativity and innovation in teaching, improving the quality of learning and student learning outcomes. The negative impact is increasing the teacher's workload in designing and implementing learning, requiring extra time and effort to study and understand the KMB, requiring intensive training and mentoring for teachers. Joint efforts are needed to ensure that the Independent Learning Curriculum can be implemented effectively and achieve its goal of improving the quality of education in Indonesia. The change in curriculum from K-13 to the Independent Learning Curriculum has both good and negative effects for teachers in junior high schools.